2014
DOI: 10.1155/2014/490318
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Fractal Description of Porosity of Coal of Different Ranks

Abstract: We selected, as the objects of our research, lignite from the Beizao Mine, gas coal from the Caiyuan Mine, coking coal from the Xiqu Mine, and anthracite from the Guhanshan Mine. We used the mercury intrusion method and the low-temperature liquid nitrogen adsorption method to analyze the structure and shape of the coal pores and calculated the fractal dimensions of different aperture segments in the coal. The experimental results show that the fractal dimension of the aperture segment of lignite, gas coal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…We used a Micromeritics Autopore ASAP 2460 adsorption instrument to carry out the LTNA and LTCA experiments in saturated liquid nitrogen at a temperature of 77 K. It needs the coal samples with 60–80 mesh by crushing and screening. The BET theory can be employed to analyze the pore area, and the BJH theory can be adopted to derive the pore volume and pore size distribution. , …”
Section: Methodsmentioning
confidence: 99%
“…We used a Micromeritics Autopore ASAP 2460 adsorption instrument to carry out the LTNA and LTCA experiments in saturated liquid nitrogen at a temperature of 77 K. It needs the coal samples with 60–80 mesh by crushing and screening. The BET theory can be employed to analyze the pore area, and the BJH theory can be adopted to derive the pore volume and pore size distribution. , …”
Section: Methodsmentioning
confidence: 99%
“…The pore volume ratio of different pore diameter segments is used as the weight value to quantitatively characterize the complexity of the coal structure and its surface roughness. The fractal dimension of different pore diameter segments is weighted and summed [34] to obtain the comprehensive fractal dimension:…”
Section: Comprehensive Fractal Dimension Of Coal Poresmentioning
confidence: 99%
“…Based on the observation of the FHH model fitting lines on the adsorption isotherms in different samples, , it is found that there is no uniform method for dividing the adsorption isotherms when this model was applied. Moreover, the division method has great effect on the calculation result of the fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 , has two linear stages, and there was a transition region between the two stages (Figure e). Type 3 has three or more linear stages (Figure f). Type 4 has no linear stage (Figure g) . In essence, method III takes the degree of linearity of the data processed by the FHH model as the selection principle for the range of isothermal adsorption data in order to obtain a reasonable fractal dimension.…”
Section: Introductionmentioning
confidence: 99%